?WRENCH ANALYSIS FOR 3-D MODEL USED IN ROBOTIC END-EFFECTOR (Biological Sciences - PJSIR, 2003)
In this paper, wrench analysis of a new proposed 3-D robotic model is discussed and applied. The model is basically used for calculating applied force through known spring stiffnesses and concerned compressive displacements. The wrench is correlated by already determined Jacobian matrix with global displacements. Local displacements are determined practi- cally by applying load vertically in centrer. The global displacements (taken as reference) are calculated by congruence matrix through wrench analysis and shown. The theoretical relationship between global displacements and individual local displacements is also calculated and shown. Besides this practical determination of the wrench analysis is also verified by applying force on any leg of the model.